Performance and Modification of Wood and Wood-Based Materials - Krystofiak, Tomasz; Bekhta, Pavlo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains 12 high-quality original research papers by 74 authors from 17 countries on 3 continents: Asia (China, Indonesia, Malaysia, and Russia), Europe (Bulgaria, the Czech Republic, Germany, Portugal, Romania, Slovakia, Slovenia, Sweden, Ukraine, and the United Kingdom), and North America (USA). These papers were published in a Special Issue, "Performance and Modification of Wood and Wood-Based Materials", of the journal Forests. They provide examples concerning conventional and novel modification processes of wood and wood-based materials, their improved/modified properties, and their relevant applications.